Effect of Low Dose Ketamine on Propofol Injection Pain: A Double-Blind Clinical Trial (KYAMC Journal, 2020)
Background: Propofol, most frequently used intravenous anesthetic for induction of routine elective surgical procedure. Pain on propofol injection (POPI) still remains a considerable concern for the anesthesiologist. A number of techniques has been tried to minimize propofol-induced pain with variable results.Objective: This study was performed to determine the effect of ketamine on reducing pain on propofol injection (POPI) at the onset of anesthesia.Materials and Methods: A total of 80 adult healthy patients were selected in this study of either sex, scheduled for routine elective ENT surgery under general anesthesia. The patients enrolled were divided randomly into two groups of 40 patients each. Group I (ketamine group) received 10 mg intravenous ketamine in 10 ml normal saline. Group II (placebo group) received 10 ml of 0.9% intravenous normal saline. Then the patients were induced with propofol and asked to report their pain during injection of propofol and recorded according to the Mc Cririck and Hunter scale.Results: The incidence of pain experienced in ketamine group was 10% patients and in saline group was 60% patients, which is statistically significant p